FLUCTUATIONS IN THE PRICE OF RESIN AND QUALITY ON THE INCOME LEVEL OF FARMERS DAMAR KRUI WEST COAST DISTRICT: PERSPECTIVE SHARIA BUSINESS MANAGEMENT - Dani Ramdani; Madnasir Madnasir; Dimas Pratomo (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
This study aims to analyze the influence of damar price fluctuations and damar quality on the income level of damar farmers in Krui District, Pesisir Barat Regency. The research employed a quantitative approach using a survey method, in which questionnaires were distributed to farmers who met the criteria as respondents. Data analysis was conducted using the Partial Least Square (PLS) method to determine the extent to which each independent variable contributes to the dependent variable. The findings indicate that price fluctuations have a positive and significant effect on farmers’ income, meaning that market price dynamics both increases and decreases directly affect the earnings received by damar farmers. In addition, damar quality also shows a positive and significant influence on income, demonstrating that higher resin quality increases both the selling value and the competitiveness of the commodity. Meanwhile, from an Islamic economic perspective, the buying and selling of damar, as long as it is carried out fairly, transparently, and free from elements of gharar, is considered a permissible form of muamalah that brings blessings to its practitioners.